2002
DOI: 10.2337/diabetes.51.5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Overt Hypoglycemia During Exercise

Abstract: These studies were conducted to determine the magnitude and mechanism of compensation for impaired glucagon and insulin responses to exercise. For this purpose, dogs underwent surgery >16 days before experiments, at which time flow probes were implanted and silastic catheters were inserted. During experiments, glucagon and insulin were fixed at basal levels during rest and exercise using a pancreatic clamp with glucose clamped (PC/GC; n ‫؍‬ 5), a pancreatic clamp with glucose unclamped (PC; n ‫؍‬ 7), or a panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In the present study, more than sixfold higher epinephrine and norepinephrine concentrations were observed during exercise at Altitude without a change in glucose R a . The role of adrenergic stimulation on hepatic glucose output during exercise is unclear; however, the data of the present study support the notion that hepatic adrenergic stimulation does not play a major role in glucose homeostasis during exercise (9,10,18).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, more than sixfold higher epinephrine and norepinephrine concentrations were observed during exercise at Altitude without a change in glucose R a . The role of adrenergic stimulation on hepatic glucose output during exercise is unclear; however, the data of the present study support the notion that hepatic adrenergic stimulation does not play a major role in glucose homeostasis during exercise (9,10,18).…”
Section: Discussionsupporting
confidence: 77%
“…Of course, this does not exclude the possibility that catecholamines are involved in the activation of hepatic MAPK signalling during exercise. Moreover, it is interesting to note that, independent of pancreatic hormones and catecholamine action, evidence exists that the fall in plasma glucose concentrations has stimulatory effects on the liver leading to enhanced glucose output [42,43]. The results from these studies suggest that a signal related to the fall in plasma glucose, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the equally rapid increase in EGP in T1D subjects during exercise despite higher glucose levels and lower glucagon concentrations, all of which would normally suppress EGP, implies that robust exercise induced hepatic responsivity despite adverse hormonal and substrate milieu, which necessitates further investigations. Factors that could contribute to this adaptive process in T1D subjects could be related to increased hepatic glucagon sensitivity stimulating glycogenolysis, increased hepatic gluconeogenesis due to enhanced substrate availability (e.g., lactate, free fatty acids), or potential blood-borne feedback and afferent mechanisms that have been shown more recently to modulate glucose R a (6,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, rates of endogenous glucose production (EGP) increase to minimize risks of hypoglycemia (5, 9, 31, 33). These changes in glucose fluxes are facilitated by falling insulin and rising glucagon and catecholamine (34) concentrations in plasma together with emerging roles for potential blood-borne feedback and afferent reflex mechanisms in stimulating glucose rate of appearance (R a ) (6,18,19) and pancreatic islet hormone secretion (24).However, the increment in EGP may not sufficiently compensate for the increase in glucose disposal, thus predisposing to exercise-induced hypoglycemia in type 1 diabetes (T1D) (27). This could, at least in part, be due to impaired glucagon and/or catecholamine secretion and responsiveness because of concomitant dysfunction of ␣-cell or autonomic systems, respectively, that often afflicts patients with T1D (8, 17).…”
mentioning
confidence: 99%
See 1 more Smart Citation